Fabrication of Cocatalyst NiO-Modified BiVO4 Composites for Enhanced Photoelectrochemical Performances - Wang, Zhi-Qiang; Wang, HongJun (Frontiers in Chemistry, 2022)
In this work, NiO modified BiVO4 (BiVO4/NiO) nanocomposite was synthesized using hydrothermal and calcination method. The composite of BiVO4/NiO, further employed as a low-overpotential photoanode, was consisted of BiVO4 nanoparticles and NiO nanosheets, in which the BiVO4 nanoelectrode served as the matrix for the attachment of NiO nanosheets. Photoelectrochemical (PEC) tests show that BiVO4/NiO displayed improved PEC performance compared with pure BiVO4. The BiVO4/NiO photoanode delivers a photocurrent density of 1.2 mA/cm2 at 1.23 V vs. RHE in a Na2SO4 electrolyte under an AM 1.5G solar simulator, which is 0.3 mA/cm2 higher than pure BiVO4 photoanode. Meanwhile, the onset potential also generates a 350 mV cathodic shift. The enhanced performance of the BiVO4/NiO nanocomposite is attributed to NiO unique lamellar structure capable of providing a large number of active sites. Measurements of electrochemical impedance spectra (EIS) and the incident photon-to-current efficiency (IPCE) illustrate that the enhanced PEC activities are ascribed to the improved charge carrier separation/transport and the promoted water oxidation kinetics furnished by the decoration of NiO cocatalyst.